The Influence of Live streaming, E-Promotions and Content Marketing on Repurchase Intentions with Customer Satisfaction as an Intervening Variable (Case Study on Local Brand Jiniso) - Herli Marlina; Mohamad Rizan; Setyo Ferry Wibowo (International Journal of Economics, Management and Accounting (IJEMA), 2024)
This research aims to determine the effect of live streaming, e-promotions and marketing content on repurchase intention with customer satisfaction as an intervening variable for the local brand Jiniso. This research uses quantitative research using purposive sampling and using a sample of 200 people. The data collection technique uses a questionnaire. Data analysis using the SEM LISREL 8.8 application. The research results show that live streaming have a positive and significant effect on repurchase intention, e-promotions have a positive and significant effect on repurchase intention, marketing content have a positive and significant effect on repurchase intention, customer satisfaction can mediate the influence of live streaming on repurchase intention. Customer satisfaction can mediate the influence of e-promotions on repurchase intention and customer satisfaction can mediate the influence of marketing content on repurchase intention.